Influence of W substitution on crystal structure, phase evolution and microwave dielectric properties of (Na0.5Bi0.5)MoO4 ceramics with low sintering temperature - Li-Xia Pang (Nature Portfolio, 2017)
Abstract In this work, the (Na0.5Bi0.5)(Mo1−xWx)O4 (x = 0.0, 0.5 and 1.0) ceramics were prepared via solid state reaction method. All the samples can be well densified at sintering temperature about ~720 °C. Dense and homogeneous microstructure with grain size lying between 2~8 μm can be observed from scanning electron microscopy (SEM). Microwave dielectric permittivity of the (Na0.5Bi0.5)(Mo0.5W0.5)O4 ceramic was found to be temperature-independent in a wide range between 25~120 °C with a temperature coefficient of frequency (TCF) ~−6 ppm/°C, a permittivity ~28.9, and Qf values 12,000~14,000 GHz. Crystal structure was refined using Rietveld method and lattice parameters are a = b = 5.281 (5) Å and c = 11.550 (6) Å with a space group I 41/a (88). The (Na0.5Bi0.5)(Mo1−xWx)O4 ceramics might be good candidate for low temperature co-fired ceramics (LTCC) technology.